Deproteinized plant juice as part of circular economy: A short review and brief experimental data - Barna, Döme; Oláhné Tóth, Ibolya; Fári, Miklós Gábor; Bákonyi, Nóra (Acta Agraria Debreceniensis, 2020)
As the population of the Earth is constantly growing it generates an unmet demand for protein, which is an urgent problem. The protein extraction process is a potential solution, which offers high-quality plant protein suitable for animal and human nutrition at a favorable price. The process used within our project produces green juice from the green alfalfa biomass through pressing. After the coagulation of protein from this green juice, the by-product is called DPJ (Deproteinized Plant Juices) or brown juice. Our preliminary results match the international literature, namely that brown juice take up as much as 50% of the fresh biomass in weight. To utilize this by-product is a crucial part of the process to make it environmental-friendly and financially viable as well. The examined brown juice samples came from a small-scale experiment of alfalfa varieties carried out in the experimental farm at the University of Debrecen. According to our preliminary results, brown juice has high macro- and micronutrient values, furthermore, it has a potentially high amount of antioxidant compounds. The study highlights that brown juice is suitable as an ingredient in microbiological media, in plant nutrition as a supplementary solution, for feedstock and for preparing human food supplements or functional foods. The potential utilization of all biorefinery products makes it a very appropriate technology for today’s challenges.